Supply response under market liberalization: a case study of Malawian agriculture - Govindan, Kumaresan; Babu, Suresh Chandra (Informa UK Limited, 2001)
In order to analyse the effects of policy reforms, output supply and factor demand responses to input and output prices for Malawian agriculture are estimated in this article in a multiple-output, multiple-input framework. The implications of various structural adjustment policies implemented in Malawi are analysed using the model results for their impact on the smallholder agricultural sector. The results of the analysis indicate that removal of fertiliser subsidy a major component of market reform policies does not substantially reduce the production of maize, the major staple food in Malawi. However, when implemented in appropriate sequence along with other output market liberalisation policies and increased investment in infrastructure, such a policy is likely to increase the productivity of smallholder agriculture.